Effect of humidifier characteristics on performance of a small-scale humidification-dehumidification desalination system. (25th June 2022) - Hussain Soomro, Saddam; Santosh, Ravichandran; Bak, Chul-U; Yoo, Chan-Ho; Kim, Woo-Seung; Kim, Young-Deuk
Highlights: A humidification–dehumidification (HDH) desalination unit was studied. The performance of the HDH unit was studied in terms of operating parameters. The effects of various hydrophobic packings on HDH performance were investigated. The mass transfer coefficient/pressure drop/productivity of the packings were studied. Abstract: Desalination, the process of obtaining potable water from seawater, has been regarded as an alternative solution to address the global issue of freshwater shortages. Considering the design, cost, and low-grade energy-driven advantages of the humidification-dehumidification (HDH) desalination process, this study aims to experimentally and theoretically investigate a laboratory-scale HDH system using different hydrophobic packing materials (i.e., hackettes, saddles, and snowflakes). We developed a mathematical model that simulates the HDH process by estimating the temperature, productivity, and gain output ratio (GOR) of each packing material and compared the results with the experimental data. The hackettes humidifier packing was found to exhibit the highest mass transfer coefficient (0.00331 kg/m 2  s), resulting in maximum productivity (0.64 kg/h at 80 ℃) and GOR (1.45 at 50 ℃). This was followed by saddle packing (0.00291 kg/m 2  s, 0.59 kg/h at 80 ℃, and 1.15 at 50 ℃, respectively), which contributed to a better HDH process than snowflakes (0.00227 kg/m 2 s, 0.56 kg/h at 80 ℃, and 1.13 at 50 ℃, respectively) due to improved heat and mass transfer efficiency in saddle packing. In addition, the effects of operating parameters (e.g., feed temperature, feed salinity, air, and water mass flow rates) on the thermal performance of HDH systems with different packings were investigated. It was confirmed that the results of the mathematical model were in good agreement with the experimental data.